A controlled release microcapsule sustained release material, preparation method and application thereof

Through the use of controlling micro -capsule indulgent materials in the repair of groundwater pollution, the unpredictable and high cost of repairing the most -release materials in existing technologies has been solved, and the controllable release of carbon sources and high -efficiency biodegradation of the halogen organic matter are realized.

CN119034634BActive Publication Date: 2025-01-28JILIN UNIVERSITY
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411524658.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-01-28
Estimated Expiration
2044-10-30

AI Technical Summary

Technical Problem

When dealing with groundwater contaminated by halogenated organic compounds, the existing technology has problems such as uncontrollable structure and performance of sustained release materials, high equipment operation and maintenance costs, and long repair cycles.

Method used

The use of controlled micro -capsule cavities, which is used as a core material for wood cellulose solid biomass material and vegetable oil, wrapped in the wall material of a single layer or multi -layer self -assembled film, and regulates micro -capsule through static electricity one by layer self -assembly technology. The size and thickness of the outer wall achieve the control of the slow -release performance.

Benefits of technology

The controllable release of carbon sources is achieved, the release cycle is extended, the biological activity of functional bacteria is enhanced, the biodegradation effect of the halogen organic matter is improved, and the problems such as reverse diffusion, drag and rebound in the long -term repair process of groundwater are solved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119034634B_ABST
    Figure CN119034634B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of groundwater pollution remediation, and in particular, relates to a controlled-release microcapsule sustained-release material, a preparation method thereof, and an application thereof. Compared with the prior art, the controlled-release microcapsule sustained-release material provided by the present invention encapsulates lignocellulosic solid biomass materials and vegetable oils, both of which, as organic carbon sources, can provide carbon sources and electron donors for functional microorganisms through slow fermentation; at the same time, the wall material is a single-layer or multi-layer self-assembled film, and by synthesizing different numbers of layers, the sustained-release speed and cycle of the microcapsule can be adjusted, thereby achieving long-term and effective enhancement of the biological activity of functional bacteria and improving the biodegradation effect of halogenated organic matter; and in view of the controllable size and sustained-release performance of the material and the stable structure, it has a high potential in practical application, and can effectively solve the problems of reverse diffusion, tailing, and rebound in the long-term remediation of groundwater.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of groundwater pollution remediation, and in particular relates to a controlled-release microcapsule sustained-release material, a preparation method thereof and an application thereof. Background Art

[0002] Halogenated organic compounds are widely used in industrial and agricultural production. They are the most common type of organic pollutants in groundwater. They are difficult to degrade, highly toxic, and easy to accumulate, posing a serious threat to human health and the ecological environment. According to statistics, the global average annual output of halogenated organic compounds has exceeded 520,000 tons, and there is still a growing trend. Halogenated hydrocarbon pollutants have been detected in the groundwater of many cities, among which chlorinated hydrocarbons have the highest detection rate, reaching 84%.

[0003] At present, a variety of remediation technologies have been developed to treat groundwater contaminated by halogenated hydrocarbons, including physical, chemical and biological remediation technologies. However, as difficult-to-degrade organic pollutants, halogenated organic compounds have a higher density than water and a strong migration ability in the underground environment. After long-term accumulation, they are prone to cause persistent pollution to the soil and various water layers. At the same time, the underground medium is non-uniform, and the shape of the pollution plume gradually becomes irregular with the increase of the non-uniformity of the aquifer medium, making its removal and monitoring work complicated. At the same time, the remediation cycle is long, and the equipment operation and maintenance costs are high. For low and medium concentration halogenated hydrocarbon pollution, compared with physical and chemical remediation, biological remediation technology has the advantages of low cost, environmental friendliness, and strong sustainability, and has become a hot spot in groundwater remediation research. Among them, microbial anaerobic reduction dehalogenation is the main process for achieving the removal of halogenated organic compounds.

[0004] The essence of microbial anaerobic reductive dehalogenation is that organic halide-respiring bacteria use organic matter and hydrogen as carbon sources and electron donors, and halogenated organic compounds as electron acceptors to achieve mineralization and degradation of halogenated organic compounds. Electron donors that can be used by organic halide-respiring bacteria are usually produced by fermentation of carbon source materials, such as lactic acid, emulsified vegetable oil, etc. However, in actual applications in contaminated sites, the cost of carbon source materials is high and they are consumed too quickly, resulting in limited sources of electron donors. In order to carry out long-term and effective bioremediation and solve the problems of reverse diffusion, tailing and rebound in the long-term remediation of groundwater, researchers use slow-release materials to provide microorganisms with a persistent carbon source and achieve a long-term supply of carbon sources and electron donors.

[0005] At present, a variety of slow-release materials have been developed, such as commercial slow-release materials: emulsified vegetable oil (EVO), emulsified oil substrate (EOS), etc.; synthetic slow-release materials: poly-γ-glutamic acid (γ-PGA), poly 3-hydroxybutyrate (PHB) and natural biomass slow-release materials: corn cobs, sawdust, peanut shells, etc. Compared with commercial slow-release materials or synthetic slow-release materials, natural biomass slow-release materials have the advantages of low cost, strong stability and high organic matter content. As a by-product of the vinegar making process, vinegar lees contains natural biomass such as sorghum and wheat bran, which can produce volatile fatty acids such as acetic acid and butyric acid and hydrogen through fermentation, providing carbon sources and electron donors for microorganisms. However, natural biomass still has certain limitations in application: ① The size is difficult to control; ② The slow-release performance is uncontrollable. Therefore, the controllable structure and slow-release performance of slow-release materials are still important bottlenecks that need to be solved urgently. It is necessary to design and develop a new type of slow-release material to achieve the controlled release of carbon sources.

[0006] The Chinese patent with publication number CN102491497A discloses a carbon source slow-release material for bioremediation of contaminated groundwater and its preparation method, wherein solid spherical solid particles with a core-shell structure are synthesized by a rolling granulation method. The core carbon-releasing raw material (bagasse) is 40%, the nutrient raw material is 1% (of which KH2PO4 is 0.5%, FeSO4·7H2O is 0.5%), the plastic bonding raw material is 45% (kaolin), the high permeability raw material is 5% (fly ash), and water is 9%. The shell carbon-releasing raw material (bagasse) is 10%, the nutrient raw material is 1% (KH2PO4 is 0.5%, FeSO4·7H2O is 0.5%), the plastic bonding raw material is 80% (ordinary Portland cement is 30%, fly ash is 50%), the high permeability raw material is 2% (diatomaceous earth), and water is 7%. While meeting the nutritional needs of microorganisms, a long-term and stable supply of groundwater remediation materials is achieved. The material has a certain mechanical strength and uniform sphericity, which overcomes the shortcomings of the conventional carbon source supplementation method, such as fast carbon source loss and fast release rate, and achieves the sustainability of the groundwater bioremediation effect. However, this technology uses a large number of difficult-to-degrade carrier materials such as fly ash and kaolin, which cannot be biodegraded and are prone to secondary environmental pollution. At the same time, the material shell is a single-layer structure, and the structure and slow-release performance are uncontrollable, which cannot meet the needs of different aquifer media.

[0007] The Chinese patent with publication number CN114656033B discloses a method for preparing a slow-release carbon source with corn cobs as the core, which uses a low-temperature freezing molding method to synthesize a cubic solid slow-release material with corn cob particles, polybutylene succinate particles, polyvinyl alcohol, and sodium alginate. The synthesized slow-release material has excellent carbon release performance, stable slow-release performance, and low cost, which reduces the cost of adding carbon sources in sewage treatment. However, the synthesis steps of this technology are cumbersome, and combined with low-temperature technology, it increases the material cost and repair cost in practical applications, and the material size and slow-release performance cannot be adjusted. Summary of the invention

[0008] In view of this, the technical problem to be solved by the present invention is to provide a controlled-release microcapsule sustained-release material with a long release period and adjustable sustained-release performance, and a preparation method and application thereof.

[0009] The invention provides a controlled-release microcapsule sustained-release material, comprising a core material and a wall material wrapped outside the core material; the core material comprises a lignocellulose solid biomass material and vegetable oil; the wall material is a single-layer or multi-layer self-assembled film; the self-assembled film is formed by self-assembly of a positively charged polyelectrolyte and a negatively charged polyelectrolyte.

[0010] Preferably, the lignocellulosic solid biomass material is selected from one or more of vinegar grains, corn cobs, straw, peanut shells, sawdust, rice husks and poplar branches;

[0011] The positively charged polyelectrolyte is selected from chitosan and / or carboxymethyl chitosan;

[0012] The negatively charged polyelectrolyte is selected from one or more of sodium carboxymethyl starch, sodium lignin sulfonate, sodium carboxymethyl cellulose, sodium alginate, gelatin and pectin.

[0013] Preferably, the particle size of the lignocellulosic solid biomass material is micrometer-sized;

[0014] The mass ratio of the lignocellulosic solid biomass material to the vegetable oil is 1:(4-20).

[0015] The present invention also provides a method for preparing a controlled-release microcapsule sustained-release material, comprising the following steps:

[0016] S1) mixing lignocellulosic solid biomass material with vegetable oil to obtain an oil phase; and using an acidic aqueous solution as a water phase;

[0017] S2) adding the oil phase to the water phase and homogenizing to obtain a Pickering emulsion stabilized by the solid biomass material;

[0018] S3) The electrostatic layer-by-layer self-assembly method is used to deposit the positively charged polyelectrolyte and the negatively charged polyelectrolyte layer by layer onto the Pickering emulsion interface stabilized by the solid biomass material to obtain a controlled release microcapsule sustained release material.

[0019] Preferably, the pH value of the aqueous phase is 4-6; the volume ratio of the oil phase to the aqueous phase is 1:(2-4).

[0020] Preferably, the homogenization speed is 5000-20000 rpm; and the homogenization time is 1-5 min.

[0021] Preferably, the step S3) is specifically as follows: under stirring, the positively charged polyelectrolyte solution and the negatively charged polyelectrolyte solution are sequentially added to the Pickering emulsion stabilized by the solid biomass material, and stirring is continued to allow the positively charged polyelectrolyte and the negatively charged polyelectrolyte to be deposited at the interface of the Pickering emulsion stabilized by the solid biomass material through electrostatic action, thereby obtaining a controlled release microcapsule sustained-release material whose wall material is a single-layer self-assembled film, and the above operation is repeated to obtain a controlled release microcapsule sustained-release material whose wall material is a multi-layer self-assembled film.

[0022] Preferably, the stirring speed is 100-500 rpm; the stirring time is 10-60 min;

[0023] The mass concentration of the positively charged polyelectrolyte in the positively charged polyelectrolyte solution is 0.1% to 0.2%;

[0024] The mass concentration of the negatively charged polyelectrolyte in the negatively charged polyelectrolyte solution is 0.1% to 1%;

[0025] The volume ratio of the positively charged polyelectrolyte solution to the negatively charged polyelectrolyte solution is (1-10):1.

[0026] Preferably, the above operation is repeated 1 to 20 times; after standing and stratifying before each repetition, the supernatant is removed and the above operation is repeated.

[0027] The present invention also provides the use of the above-mentioned controlled-release microcapsule sustained-release material as a carbon source for groundwater pollution remediation.

[0028] The present invention provides a controlled-release microcapsule sustained-release material, comprising a core material and a wall material wrapped outside the core material; the core material comprises a lignocellulosic solid biomass material and a vegetable oil; the wall material is a single-layer or multi-layer self-assembled membrane; the self-assembled membrane is formed by self-assembly of a positively charged polyelectrolyte and a negatively charged polyelectrolyte. Compared with the prior art, the controlled-release microcapsule sustained-release material provided by the present invention encapsulates a lignocellulosic solid biomass material and a vegetable oil, both of which, as organic carbon sources, can provide a carbon source and an electron donor for functional microorganisms through slow fermentation; at the same time, the wall material is a single-layer or multi-layer self-assembled membrane, and the sustained-release speed and cycle of microcapsules with different numbers of layers are different, which can effectively enhance the biological activity of functional bacteria for a long time and improve the biodegradation effect of halogenated organic matter; and in view of the controllable size and sustained-release performance of the material and the stable structure, it has a high potential in practical application and can effectively solve the problems of reverse diffusion, tailing and rebound in the long-term restoration of groundwater. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 A schematic diagram of the preparation process of a Pickering emulsion stabilized by a solid biomass material when the solid biomass material provided by the present invention is vinegar grains;

[0030] Figure 2 A schematic diagram of the preparation process of the controlled-release microcapsule sustained-release material provided by the present invention;

[0031] Figure 3 A schematic diagram of using the controlled-release microcapsule sustained-release material provided by the present invention as a carbon source for groundwater pollution remediation;

[0032] Figure 4 The graphs are the contact angles of vinegar lees at different interfaces during the synthesis of the vinegar lees-based Pickering emulsion obtained in Example 1 of the present invention, the fluorescence microscope graph of the Pickering emulsion, and the optical microscope graph of the Pickering emulsion; wherein a is the contact angle graph of the vinegar lees, b is the fluorescence microscope graph of the Pickering emulsion, and c is the optical microscope graph of the Pickering emulsion;

[0033] Figure 5 The optical microscope images of the vinegar lees-based Pickering emulsion under different synthesis conditions in Example 1 of the present invention; wherein a represents different particle concentrations, b represents different grinding times, c represents different oil-water volume ratios, d represents different homogenization speeds, and e represents different homogenization times;

[0034] Figure 6 The morphology of the vinegar dregs microcapsules with different shell layers obtained in Example 1 of the present invention; a is an optical microscope image of the microcapsules with different shell layers, and b is a particle size distribution diagram of the microcapsules with different shell layers;

[0035] Figure 7It is a fitting curve diagram of the sustained-release kinetic model of vinegar dregs microcapsules with different shell layer numbers obtained in Example 1 of the present invention; wherein a is a fitting curve diagram of VR (CS + CMS) 0@PE microcapsules, b is a fitting curve diagram of VR (CS + CMS) 4@PE microcapsules, c is a fitting curve diagram of VR (CS + CMS) 8@PE microcapsules, and d is a fitting curve diagram of VR (CS + CMS) 12@PE microcapsules;

[0036] Figure 8 This is a graph showing the content of small molecular organic acids produced by anaerobic fermentation of vinegar grains obtained in Example 1 of the present invention. DETAILED DESCRIPTION

[0037] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0038] The invention provides a controlled-release microcapsule sustained-release material, comprising a core material and a wall material wrapped outside the core material; the core material comprises a lignocellulose solid biomass material and vegetable oil; the wall material is a single-layer or multi-layer self-assembled film; the self-assembled film is formed by self-assembly of a positively charged polyelectrolyte and a negatively charged polyelectrolyte.

[0039] The controlled-release microcapsule sustained-release material provided by the present invention comprises a core material; the core material comprises a lignocellulose solid biomass material and vegetable oil.

[0040] According to the present invention, the lignocellulosic solid biomass material is preferably one or more of vinegar lees, corn cobs, straw-like materials, peanut shells, sawdust, rice husks and poplar branches; the straw-like materials are straw-like materials well known to those skilled in the art, and are not particularly limited. In the present invention, it is preferably one or more of rice straw, wheat straw and corn straw; in the present invention, the lignocellulosic solid biomass material is most preferably vinegar lees, which is the residue after fermentation, brewing and extracting vinegar with rice bran, bran and sorghum husk as raw materials. As an industrial waste, it has a wide source and low cost. Vinegar lees contains lignocellulose and a variety of nutrients, has a wide source and low cost, and has a high content of cellulose and hemicellulose, a low content of lignin, and is easily degraded and utilized by microorganisms. Fermentation produces volatile fatty acids such as acetic acid and butyric acid and hydrogen, which can provide carbon sources and electron donors for organic halide respiratory bacteria to stimulate the growth of organic halide respiratory bacteria. At the same time, vinegar lees contains some nutrients, such as sulfate, which can promote microbial activity.

[0041] According to the present invention, the particle size of the lignocellulosic solid biomass material is preferably micrometer-sized, more preferably less than 100 micrometers, further preferably less than 50 micrometers, and most preferably less than 10 micrometers.

[0042] According to the present invention, the vegetable oil can be any vegetable oil well known to those skilled in the art without any special limitation. In the present invention, it is preferably one or more of peanut oil, rapeseed oil, cottonseed oil, sunflower seed oil, linseed oil, corn oil and soybean oil; in the embodiments provided in the present invention, soybean oil is specifically used as an example for description.

[0043] According to the present invention, the mass ratio of the lignocellulosic solid biomass material to the vegetable oil is preferably 1:(4-20), more preferably 1:(4-15), further preferably 1:(4-10), and most preferably 1:4.

[0044] According to the present invention, in view of the different nutrient matrices required by different functional bacterial communities, the core material may preferably further include different types of nutrients, such as fat-soluble vitamins or other solid substances.

[0045] The core material of the controlled release microcapsule sustained-release material provided by the present invention is wrapped with a wall material; the wall material is a single-layer or multi-layer self-assembled film; the number of layers of the multi-layer self-assembled film is preferably 2 to 20 layers, more preferably 2 to 18 layers, more preferably 4 to 16 layers, more preferably 4 to 14 layers, and most preferably 4 to 12 layers; in some embodiments provided by the present invention, the number of layers of the multi-layer self-assembled film is specifically 4, 8 or 12 layers.

[0046] According to the present invention, the self-assembled film is formed by self-assembly of a positively charged polyelectrolyte and a negatively charged polyelectrolyte; the positively charged polyelectrolyte is preferably chitosan and / or a chitosan derivative, more preferably chitosan and / or carboxymethyl chitosan; chitosan and / or a chitosan derivative has pH sensitivity, which can make the controlled release microcapsule sustained release material have a certain pH responsiveness, thereby realizing the intelligent release of the sustained release carbon source; the negatively charged polyelectrolyte is preferably one or more of sodium carboxymethyl starch, sodium lignin sulfonate, sodium alginate, gelatin and pectin; the mass ratio of the positively charged polyelectrolyte to the negatively charged polyelectrolyte is preferably 1: (0.5-2), more preferably 1: (0.8-1.5), more preferably 1: (0.8-1.2), and most preferably 1: 1.

[0047] According to the present invention, the release behavior of the controlled-release microcapsule sustained-release material conforms to the Korsmeyer-Peppas model, and its release index is between 0.45 and 0.89.

[0048] The controlled-release microcapsule sustained-release material provided by the present invention encapsulates lignocellulosic solid biomass material and vegetable oil inside, and both of them, as organic carbon sources, can provide carbon sources and electron donors for functional microorganisms through slow fermentation; at the same time, the wall material is a single-layer or multi-layer self-assembled film, and the sustained-release speed and cycle of microcapsules with different numbers of layers are different, which can effectively enhance the biological activity of functional bacteria and improve the biodegradation effect of halogenated organic matter for a long time; and in view of the controllable size and sustained-release performance of the material and the stable structure, it has high potential in practical application and can effectively solve the problems of reverse diffusion, tailing and rebound in the long-term restoration process of groundwater.

[0049] The present invention also provides a method for preparing a controlled-release microcapsule sustained-release material, comprising the following steps: S1) mixing a lignocellulosic solid biomass material with a vegetable oil to obtain an oil phase; using an acidic aqueous solution as an aqueous phase; S2) adding the oil phase to the aqueous phase for homogenization to obtain a Pickering emulsion that is stable to the solid biomass material; S3) using an electrostatic layer-by-layer self-assembly method to deposit a positively charged polyelectrolyte and a negatively charged polyelectrolyte layer by layer to the interface of the Pickering emulsion that is stable to the solid biomass material to obtain a controlled-release microcapsule sustained-release material.

[0050] Pickering emulsion microcapsules are synthesized using lignocellulosic solid biomass particles, and lignocellulosic solid biomass is simultaneously encapsulated inside the microcapsules, thereby extending the carbon source release period. However, the wall thickness of the microcapsules is difficult to adjust, making it impossible to achieve adjustable sustained-release performance. Therefore, the present invention utilizes electrostatic layer-by-layer self-assembly technology to change the size of the microcapsules and the thickness of the outer wall, thereby achieving adjustable sustained-release performance. During the release process of the Pickering emulsion stabilized by solid biomass materials, the outer shell is easily broken and the carbon source is released at a faster rate. As the number of outer shell layers increases, the microcapsule structure becomes more stable and the carbon source release rate slows down. This indicates that the sustained-release performance of the material can be regulated by changing the number of outer wall layers of the microcapsules. At the same time, the change in the number of outer shell layers makes the size structure of the microcapsules adjustable to meet the needs of different hydrogeological conditions.

[0051] The present invention has no particular limitation on the sources of all raw materials, and any raw materials available on the market can be used.

[0052] Mixing lignocellulosic solid biomass material with vegetable oil to obtain an oil phase; the lignocellulosic solid biomass material and the vegetable oil are the same as described above and will not be repeated here; the lignocellulosic solid biomass material is preferably obtained by drying, crushing and grinding the solid biomass material; the grinding time is preferably 0.5~2 h, more preferably 0.5~1.5 h, more preferably 0.8~1.2 h, and most preferably 1 h; the mass concentration of the lignocellulosic solid biomass material in the oil phase is preferably 5.0%~30%, more preferably 20%~25%, and more preferably 25%.

[0053] The present invention uses an acidic aqueous solution as the aqueous phase; the pH value of the aqueous phase is preferably 4-6, more preferably 4.5-5.5, and even more preferably 5; the acidic aqueous solution is preferably a hydrochloric acid aqueous solution.

[0054] After adding the oil phase to the water phase for homogenization, a Pickering emulsion stable with solid biomass material is obtained; the volume ratio of the oil phase to the water phase is preferably 1:(2-4), more preferably 1:3; the speed of the homogenization is preferably 5000-20000 rpm, more preferably 5000-15000 rpm, more preferably 8000-12000 rpm, and most preferably 10000 rpm; the homogenization time is preferably 1-5 min, more preferably 1-4 min, and more preferably 2-3 min. See Figure 1 , Figure 1 The figure is a schematic diagram of the preparation process of Pickering emulsion stabilized by solid biomass material when the solid biomass material is vinegar grains.

[0055] By adopting the electrostatic layer-by-layer self-assembly method, the positively charged polyelectrolyte and the negatively charged polyelectrolyte are deposited layer by layer to the Pickering emulsion interface of the solid biomass material to obtain a controlled release microcapsule sustained-release material. In the present invention, this step is specifically as follows: under stirring, the positively charged polyelectrolyte solution and the negatively charged polyelectrolyte solution are sequentially added to the Pickering emulsion stabilized by the solid biomass material, and stirring is continued to allow the positively charged polyelectrolyte and the negatively charged polyelectrolyte to be deposited to the Pickering emulsion interface of the solid biomass material through electrostatic action to obtain a controlled release microcapsule sustained-release material whose wall material is a single-layer self-assembled film, and the above operation is repeated to obtain a controlled release microcapsule sustained-release material whose wall material is a multi-layer self-assembled film. See Figure 2 , Figure 2 Schematic diagram of the preparation process of controlled-release microcapsule sustained-release materials.

[0056] According to the present invention, the mass concentration of the positively charged polyelectrolyte in the positively charged polyelectrolyte solution is preferably 0.1% to 0.2%; the positively charged polyelectrolyte solution is preferably prepared according to the following steps: mixing the positively charged polyelectrolyte with an acetic acid aqueous solution to obtain a positively charged polyelectrolyte solution; the volume ratio of acetic acid in the acetic acid aqueous solution is preferably 1% to 5%, more preferably 1% to 3%, and further preferably 2%; the positively charged polyelectrolyte is the same as described above and will not be repeated here.

[0057] According to the present invention, the mass concentration of the negatively charged polyelectrolyte in the negatively charged polyelectrolyte solution is preferably 0.1% to 1%, more preferably 0.2% to 0.8%, further preferably 0.2% to 0.6%, and most preferably 0.4%; the negatively charged polyelectrolyte solution is preferably prepared according to the following steps: mixing the negatively charged polyelectrolyte with water to obtain a negatively charged polyelectrolyte solution.

[0058] Under stirring conditions, a positively charged polyelectrolyte solution and a negatively charged polyelectrolyte solution are sequentially added to a Pickering emulsion stabilized by a solid biomass material; the stirring speed is preferably 100-500 rpm, more preferably 200-400 rpm, and even more preferably 300 rpm; the volume ratio of the positively charged polyelectrolyte solution to the negatively charged polyelectrolyte solution is preferably (1-10):1, more preferably (2-8):1, even more preferably (2-6):1, even more preferably (3-5):1, and most preferably 4:1; the volume ratio of the positively charged polyelectrolyte solution to the Pickering emulsion stabilized by a solid biomass material is preferably 1:(1-3), more preferably 1:2.

[0059] Continue stirring to allow the positively charged polyelectrolyte and the negatively charged polyelectrolyte to be deposited at the Pickering emulsion interface stabilized by the solid biomass material through electrostatic action, thereby obtaining a controlled release microcapsule sustained-release material whose wall material is a single-layer self-assembled film; the time for continuing stirring is preferably 10 to 60 min, more preferably 20 to 50 min, more preferably 20 to 40 min, and most preferably 30 min.

[0060] Repeat the above operation, i.e., repeatedly add the positively charged polyelectrolyte solution and the negatively charged polyelectrolyte solution and continue stirring to obtain a controlled release microcapsule sustained release material whose wall material is a multilayer self-assembled film; the number of repetitions is preferably 1 to 20 times, more preferably 1 to 17 times, more preferably 3 to 15 times, more preferably 3 to 13 times, and most preferably 3 to 11 times.

[0061] In a specific embodiment provided by the present invention, before each repetition, preferably after standing and stratification, the lower supernatant is removed, and the above operation is repeated to obtain a controlled release microcapsule sustained release material whose wall material is a multilayer self-assembled film.

[0062] The present invention also provides an application of the above-mentioned controlled-release microcapsule slow-release material as a carbon source for groundwater pollution remediation. Figure 3 , Figure 3 This is a schematic diagram of using the controlled-release microcapsule sustained-release material provided by the present invention as a carbon source for groundwater pollution remediation.

[0063] More specifically, the groundwater pollution remediation is in situ bioremediation.

[0064] More specifically, the groundwater pollution is halogenated organic compound pollution.

[0065] In order to further illustrate the present invention, a controlled release microcapsule sustained-release material, a preparation method thereof and an application thereof provided by the present invention are described in detail below in conjunction with examples.

[0066] The reagents used in the following examples are all commercially available; the degree of polymerization and deacetylation of the chitosan used in the examples are ≥95%, and the viscosity is 100-200 mpa.s; the degree of substitution of the sodium carboxymethyl starch used is 0.35-0.5; and the vinegar dregs are wastes generated by the aged vinegar brewing industry.

[0067] Example 1

[0068] 1.1 After drying and crushing the vinegar lees, use a ball mill to ball mill, and then grind for 1 hour to make the vinegar lees particle size less than 10 microns. Pour the vinegar lees into soybean oil and stir to mix well, as the oil phase, the vinegar lees concentration in the oil phase is 25 wt.%; adjust the pH of deionized water to 5 with hydrochloric acid, as the water phase; after pouring the oil phase into the water phase (the volume ratio of the two is 1:3), use a homogenizer at a speed of 10000 rpm for 2 minutes to obtain a vinegar lees Pickering emulsion.

[0069] Different particle concentrations (5 wt.%, 10 wt.%, 25 wt.%), different grinding times (0 h, 0.5 h, 1 h), different oil-water volume ratios (1:1, 1:2, 1:3), different homogenization speeds (6000 rpm, 8000 rpm, 10000 rpm) and different homogenization times (1 min, 2 min, 4 min) were set to adjust the synthesis of Pickering emulsion. The optimal synthesis conditions were as follows: vinegar lees concentration of 25 wt.%, grinding for 1 hour, oil-water volume ratio of 1:3, homogenization speed of 10000 rpm and homogenization time of 2 min.

[0070] 1.2 Dissolve chitosan in 2% by volume acetic acid aqueous solution to prepare a chitosan solution with a mass fraction of 0.1%. Dissolve sodium carboxymethyl starch in deionized water to prepare a sodium carboxymethyl starch solution with a mass fraction of 0.4%. The vinegar lees Pickering emulsion was magnetically stirred at a speed of 300 rpm, and the chitosan solution and the sodium carboxymethyl starch solution were sequentially added to the Pickering emulsion in a volume ratio of 4:1 (the volume ratio of chitosan solution to Pickering emulsion was 1:2), and stirred for 30 min to allow chitosan and sodium carboxymethyl starch to be deposited on the interface of the Pickering emulsion through electrostatic action to form a single-layer microcapsule VR (CS + CMS) 1 @ PE. The above steps constitute one cycle. After the end, the solution is allowed to stand for a period of time. After the solution is completely separated, the supernatant is removed and the above steps are repeated n times to prepare n-layer microcapsules containing n layers of chitosan and n layers of sodium carboxymethyl starch, which are defined as VR (CS + CMS) n @PE. Composite materials with 0, 4, 8, and 12 layers are selected.

[0071] Synthesis conditions of vinegar lees-based Pickering emulsion:

[0072] In order to evaluate the properties of vinegar lees solid particles, the surface wettability of vinegar lees solid particles was tested. To further determine the type of Pickering emulsion formed, soybean oil was stained with Nile red, the material structure was observed under a fluorescence microscope, and the morphology of the final synthesized Pickering emulsion was observed using an optical electron microscope. The contact angles of vinegar lees at different interfaces during the synthesis of vinegar lees-based Pickering emulsion, the fluorescence microscope images of Pickering emulsion, and the optical microscope images of Pickering emulsion were obtained as shown in the figure. Figure 4 As shown, (a) is the contact angle diagram of vinegar residue, (b) is the fluorescence microscope diagram of Pickering emulsion, and (c) is the optical microscope diagram of Pickering emulsion. Figure 4 In (a), it can be seen that the two-phase contact angle and the three-phase contact angle of the vinegar lees particles are both less than 90°, so it is easier to form a water-in-oil structure. From the picture obtained by fluorescence microscopy (b), it can be seen that the dyed oil phase is all over the microcapsule, verifying that the Pickering emulsion is a water-in-oil structure. From the optical microscopy picture (c), it can be seen that the prepared Pickering emulsion has a uniform size and successfully encapsulates the vinegar lees particles inside.

[0073] In order to evaluate the effects of particle concentration, grinding time, oil-water volume ratio, homogenization speed, and homogenization time on the uniformity and stability of Pickering emulsions, the morphologies of Pickering emulsions obtained under different synthesis conditions were observed using a microscope, e.g. Figure 5 As shown, (a) is different particle concentration, (b) is different grinding time, (c) is different oil-water volume ratio, (d) is different homogenization speed, and (e) is different homogenization time. It can be seen from the figure that when the vinegar residue concentration is 25 wt.%, the grinding is 1 hour, the oil-water volume ratio is 1:3, the homogenization speed is 10000 rpm, and the homogenization time is 2 min, the Pickering emulsion structure is complete and the size is uniform, which is the optimal synthesis condition.

[0074] VR (CS + CMS) n @PE different shell layer morphology observation conditions setting:

[0075] In order to evaluate the structural differences of VR (CS + CMS) n @PE with different numbers of shell layers, the synthesized controlled-release microcapsules with different numbers of shell layers were observed under an optical microscope. 2 g of VR (CS + CMS) n @PE was resuspended in deionized water. After standing for 5 min, the solid particles that settled to the bottom of the solution were removed, and the suspended VR (CS + CMS) n @PE was placed on a glass slide. The morphological characteristics were observed under an optical microscope, and the size of the microcapsules with different numbers of shell layers was measured. The morphology of the microcapsules with different numbers of shell layers is shown in Figure 2. Figure 6 As shown, (a) is an optical microscope image of microcapsules with different numbers of shell layers, and (b) is a particle size distribution diagram of microcapsules with different numbers of shell layers. Figure 6It can be seen that the thickness of the microcapsule shell gradually increases with the increase of the number of deposition layers. With the increase of the number of shell layers, the content of vinegar residue encapsulated therein decreases slightly. The size of the microcapsule increases with the increase of wall thickness, indicating that this method can synthesize sustained-release materials with different shell thicknesses and different sizes to achieve controlled release of sustained-release carbon sources.

[0076] VR (CS + CMS) n @PE sustained release performance test conditions setting:

[0077] In order to evaluate the release behavior of the prepared VR (CS + CMS) n @ PE, 2 g of VR (CS + CMS) n @ PE (n = 0, 4, 8, 12) with different shell layers was added to a serum bottle, 80 ml of deionized water was poured in, the material was suspended in water, and then sealed and placed in a constant temperature shaking incubator with an oscillation rate of 100 rmp and a temperature of 25 ° C. Samples were taken at fixed time points (0 days, 0.5 days, 1 day, 2 days, 4 days, 6 days, 8 days, 12 days, 16 days, 20 days, 25 days, 30 days, 40 days, 50 days, 60 days), and the samples were collected and filtered to test the TOC content. The material morphology was observed under an optical microscope at 15 days. The cumulative release of VR (CS + CMS) 0 @ PE within 60 days reached 117 mg / L, and the cumulative release growth trend slowed down after the 20th day. In contrast, the VR (CS + CMS) 12 @ PE system with a solid multi-layer outer wall structure effectively prolonged the release time of organic matter. The cumulative release within 60 days was 80.2 mg / L, which is 0.69 times the cumulative release of VR (CS + CMS) 0 @ PE, and is still in an increasing state, which is more conducive to the long-term supply of carbon sources. In addition, when the release amount is the same, the more microcapsule layers there are, the longer the release time required, indicating that the release rate of organic matter can be well controlled by changing the number of microcapsule shell layers. In order to understand the release behavior of the microcapsules, the zero-order, first-order, Higuchi and Korsmeyer-Peppas kinetic models were applied to fit the sustained-release data, and the fitting curve of the sustained-release kinetic model was obtained as shown in the figure. Figure 7 As shown, Figure 7 a is the fitting curve of VR (CS + CMS) 0@PE microcapsule, b is the fitting curve of VR (CS + CMS) 4@PE microcapsule, c is the fitting curve of VR (CS + CMS) 8@PE microcapsule, and d is the fitting curve of VR (CS + CMS) 12@PE microcapsule. Figure 7The fitting results show that the release behavior of VR (CS + CMS) 0 @ PE microcapsules conforms to the first-order kinetics. The thinner shell makes the material easy to rupture and releases faster. As the number of shell layers increases, the release behavior of 4, 8, and 12-layer microcapsules conforms to the Korsmeyer-Peppas model, and the diffusion index is between 0.45 and 0.89, indicating that there are two mechanisms of release: diffusion and dissolution. As the number of layers increases, the index gradually increases, indicating that as the thickness of the shell increases, the encapsulation performance is improved, and the internal carbon source can only be released after the shell is destroyed. These results show that the sustained-release performance of the prepared VR (CS + CMS) n @ PE is controllable, and as the number of shell layers increases, the release kinetics changes, and the release rate decreases significantly, indicating that the prepared sustained-release material can provide a sustainable carbon source supply for microorganisms and improve the bioremediation effect.

[0078] Vinegar lees fermentation performance test conditions setting:

[0079] In order to explore the potential of vinegar lees to enhance the functional microorganisms to degrade halogenated hydrocarbons, the acid production performance of vinegar lees fermentation was investigated. The fermentation experiment used 100 mL serum bottles, each bottle was filled with 2 g of vinegar lees, and 80 mL of actual groundwater was added for anaerobic culture in the dark (simulating groundwater environment). Samples were taken from the bottles regularly, and the volatile organic fatty acid content of the samples was tested after the samples were filtered. The content of small molecular organic acids produced by anaerobic fermentation of vinegar lees is shown in the figure below. Figure 8 As shown. Fermentation test results Figure 8 It can be seen that vinegar grains can produce a large amount of fatty acids under anaerobic conditions. Due to the low biomass of groundwater, the fermentation starts slowly and can continue to produce acid for more than 80 days. The acid production cycle is relatively long and shows a steady upward trend, which can stably provide the required carbon source for microorganisms.

[0080] The above results show that the contact angle of vinegar dregs as solid particles stabilizing Pickering emulsions is less than 90°, which is conducive to the construction of water-in-oil Pickering emulsions. The prepared VR (CS + CMS) n @PE has good controlled release properties. The release rate of the carbon source can be controlled by adjusting the size and wall thickness of the microcapsules. As the size and wall thickness of the microcapsules increase, the release rate tends to decrease. The experimental results preliminarily show that VR (CS + CMS) n @PE has good controlled release properties and can achieve controlled release of nutrient matrix. At the same time, vinegar dregs as a slow-release matrix can provide carbon source and electron donor for microorganisms through fermentation.

[0081] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A controlled release microcapsule sustained release material, characterized in that: It comprises a core material and a wall material wrapped outside the core material; the core material comprises a wood cellulose solid biomass material and vegetable oil; the wall material is a single-layer or multi-layer self-assembled film; the self-assembled film is formed by self-assembly of a positively charged polyelectrolyte and a negatively charged polyelectrolyte.

2. The controlled release microcapsule sustained release material according to claim 1, characterized in that: The lignocellulosic solid biomass material is selected from one or more of vinegar dregs, corn cobs, straw, peanut shells, sawdust, rice husks and poplar branches; The positively charged polyelectrolyte is selected from chitosan and / or carboxymethyl chitosan; The negatively charged polyelectrolyte is selected from one or more of sodium carboxymethyl starch, sodium lignin sulfonate, sodium carboxymethyl cellulose, sodium alginate, gelatin and pectin.

3. The controlled release microcapsule sustained release material according to claim 1, characterized in that: The particle size of the lignocellulosic solid biomass material is micrometer-sized; The mass ratio of the lignocellulosic solid biomass material to the vegetable oil is 1:(4-20).

4. A method for preparing a controlled release microcapsule sustained-release material, characterized in that: The following steps are involved: S1) mixing lignocellulosic solid biomass material with vegetable oil to obtain an oil phase; The acidic aqueous solution is used as the water phase; S2) adding the oil phase to the water phase and homogenizing to obtain a Pickering emulsion stabilized by the solid biomass material; S3) The electrostatic layer-by-layer self-assembly method is used to deposit the positively charged polyelectrolyte and the negatively charged polyelectrolyte layer by layer onto the Pickering emulsion interface stabilized by the solid biomass material to obtain a controlled release microcapsule sustained release material.

5. The preparation method according to claim 4, characterized in that: The pH value of the water phase is 4-6; the volume ratio of the oil phase to the water phase is 1:(2-4).

6. The preparation method according to claim 4, characterized in that: The homogenizing speed is 5000-20000 rpm; the homogenizing time is 1-5 min.

7. The preparation method according to claim 4, characterized in that: The step S3) is specifically as follows: under stirring, the positively charged polyelectrolyte solution and the negatively charged polyelectrolyte solution are sequentially added to the Pickering emulsion stabilized by the solid biomass material, and stirring is continued to allow the positively charged polyelectrolyte and the negatively charged polyelectrolyte to be deposited at the interface of the Pickering emulsion stabilized by the solid biomass material through electrostatic action, thereby obtaining a controlled release microcapsule sustained-release material whose wall material is a single-layer self-assembled film, and the above operation is repeated to obtain a controlled release microcapsule sustained-release material whose wall material is a multi-layer self-assembled film.

8. The preparation method according to claim 7, characterized in that: The stirring speed is 100-500 rpm; the stirring time is 10-60 min; The mass concentration of the positively charged polyelectrolyte in the positively charged polyelectrolyte solution is 0.1% to 0.2%; The mass concentration of the negatively charged polyelectrolyte in the negatively charged polyelectrolyte solution is 0.1% to 1%; The volume ratio of the positively charged polyelectrolyte solution to the negatively charged polyelectrolyte solution is (1-10):

1.

9. The preparation method according to claim 7, characterized in that: The above operation is repeated 1 to 20 times; after standing and stratifying before each repetition, the supernatant is removed and the above operation is repeated.

10. Use of the controlled-release microcapsule sustained-release material according to any one of claims 1 to 3 or the controlled-release microcapsule sustained-release material prepared by the preparation method according to any one of claims 4 to 9 as a carbon source for groundwater pollution remediation.

Citation Information

Patent Citations

  • Controlled-release carbon source material for repairing polluted underground water organisms and preparation method thereof

    CN102491497A

  • A method for preparing a slow-release carbon source based on corn cob.

    CN114656033B

  • Method for preparing core-shell structure nano microcapsule

    CN101259400A

  • Slow-release compound repair material for treating chlorine-containing organic pollutants in groundwater and preparation method thereof

    CN104944568A